Induction of mesenchymal stem cell differentiation by co-culturing with mature cells in double-layered 2-methacryloyloxyethyl phosphorylcholine polymer hydrogel matrices. Issue 14 (8th December 2021) - Ishihara, Kazuhiko; Kaneyasu, Miu; Fukazawa, Kyoko; Zhang, Ren; Teramura, Yuji
Abstract : Mesenchymal stem cells can be encapsulated 3-dimensionally in a spontaneously forming polymer hydrogel. Differentiation of the cells is effectively induced by close-contact co-culturing with mature cells encapsulated in different polymer hydrogels. Abstract : The effects of differentiated cells on stem cell differentiation were analyzed via co-culturing using a cell-encapsulated double-layered hydrogel system. As a polymer hydrogel matrix, a water-soluble zwitterionic polymer having both a 2-methacryloyloxyethyl phosphorylcholine unit and a p -vinylphenylboronic acid unit (PMBV), was complexed spontaneously with poly(vinyl alcohol) (PVA) under mild cell culture conditions. The creep modulus of the hydrogel was controlled by changing the composition of the polymer in the solution. Mouse mesenchymal stem cells (MSCs), C3H10T1/2 cells, were encapsulated into PMBV/PVA hydrogels and cultured. In the PMBV/PVA hydrogel with a lower creep modulus (0.40 kPa), proliferation of C3H10T1/2 cells occurred, and the formation of cell aggregates was observed. On the other hand, a higher creep modulus (1.7 kPa) of the hydrogel matrix prevented cell proliferation. Culturing C3H10T1/2 cells encapsulated in the PMBV/PVA hydrogel in the presence of bone morphogenetic protein-2 increased the activity of intracellular alkaline phosphatase (ALP). This indicated that C3H10T1/2 cells differentiated into mature osteoblasts. When the C3H10T1/2 cells encapsulated in the PMBV/PVA hydrogel were cultured in combination with the mature osteoblasts in the hydrogel by a close contacting double-layered hydrogel structure, higher ALP activity was observed compared with the cells cultured separately. It was considered that the differentiation of C3H10T1/2 cells in the hydrogel layer was induced by cytokines diffused from mature osteoblasts encapsulated in another hydrogel layer. It could be concluded that the PMBV/PVA hydrogel system provides a good way to observe the effects of the surrounding cells on cell function in three-dimensional culture.